2015
DOI: 10.1002/oby.21168
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations of eating behaviors with weight gain in infants

Abstract: Objective To examine whether maternal reports of infant eating behaviors are stable over time and whether eating behaviors are prospectively associated with weight gain. Methods In an ongoing study of infant growth, weight and length were measured at 2-weeks, 3-months, and 5-months of age. Food responsiveness (FR), satiety responsiveness (SR), enjoyment of feeding (EF), and slow eating (SE) were assessed with the Baby Eating Behavior Questionnaire. Repeated measures ANOVA were used to examine changes in eati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 42 publications
2
17
1
1
Order By: Relevance
“…To date, the stability of the appetitive traits from childhood to adulthood has not been studied, with the exception of picky eating, which has been shown to persist across childhood [ 18 ] and into young adulthood [ 25 ]. Other appetitive traits have shown stability from birth to 10 years old [ 21 , 26 , 27 ]. In addition, all of these traits show evidence of high heritability, suggesting that they are best thought of as stable traits that are expressed relatively similarly across the lifespan [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the stability of the appetitive traits from childhood to adulthood has not been studied, with the exception of picky eating, which has been shown to persist across childhood [ 18 ] and into young adulthood [ 25 ]. Other appetitive traits have shown stability from birth to 10 years old [ 21 , 26 , 27 ]. In addition, all of these traits show evidence of high heritability, suggesting that they are best thought of as stable traits that are expressed relatively similarly across the lifespan [ 28 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Third, because of the observational nature of the study with energy intake and satiety responsiveness not measured until 5 years of age, we cannot infer causality. Although the temporal order of our findings suggests an effect of early weight gain on later energy intake and satiety response, a recent study suggested reversed causality: i.e., that infants may already have an increased energy intake and diminished satiety response leading to subsequent increased infant and childhood weight gain [ 51 ]. Studies are currently underway that aim to capture feeding practices and eating behaviors from infancy onwards and relate them to future growth [ 52 ].…”
Section: Discussionmentioning
confidence: 90%
“…This is the first study to examine relationships between HMOs and infant eating behavior. In particular, we examined food responsiveness, which has previously been shown to positively predict rapid infant weight gain 17‐20 —an established risk factor for later obesity 21‐23 . We hypothesized that LNFPII would be associated with reduced food responsiveness at 1 month, based on our previous analysis of weight change between 1 and 6 months in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The BEBQ measures an infant's food responsiveness (ie, drive to eat), enjoyment of food, general appetite, satiety responsiveness (ie, response to fullness) and speed of eating 16 . Greater enjoyment of food, quicker eating, reduced satiety responsiveness and increased food responsiveness scores on the BEBQ have all been associated with rapid weight gain in infancy 17‐20 —a risk factor for childhood and adult obesity 21‐23 …”
Section: Introductionmentioning
confidence: 99%